Marketing Mix Implementation on Products, Prices, Places, Promotions In Marketing of Education Services - Nurman, Amril; Harapan, Edi (Jurnal Pendidikan Tambusai, 2021)
This article aims to describe the implementation of the marketing mix in product, price, place and promotion in the marketing of educational services.